Effect of Repetitive Transcranial Magnetic Stimulation in Inducing Weight Loss in Patients with Chronic Schizophrenia: A Randomized, Double-Blind Controlled 4-Week Study - Su, Xiuru; Wang, Xuan; Pan, Xiuling; Zhang, Xuan; Lu, Xinyan; Zhao, Long; Chen, Yingnan; Shang, Yujie; Zhu, Lin; Lu, Shulan; Zhu, Xiaolin; Wu, Fengchun; et al. (Current Neuropharmacology, 2023)
Objectives: There is emerging evidence that high-frequency (HF) repetitive transcranial magnetic stimulation (rTMS) may promote weight loss in individuals with obesity in the general population. However, no study has been conducted on patients with schizophrenia (SZ). This study evaluated the efficacy of 10Hz rTMS in reducing body weight in patients with chronic SZ. Methods: Forty-seven SZ patients were randomly assigned to two groups: 10Hz rTMS or sham stimulation over DLPFC (applied once daily) for 20 consecutive treatments. Body weight was assessed at baseline, at the end of week 1, week 2, week 3 and week 4. Clinical symptoms were evaluated with the Positive and Negative Syndrome Scale (PANSS) at baseline and at the end of week 4. Results: We found that compared with patients in the sham group, 10Hz rTMS treatment significantly reduced body weight in patients with chronic SZ after a period of 4 weeks of stimulation. Interestingly, further analysis found that from the first week (5 sessions) of treatment, there was a significant difference in body weight between active and sham groups after controlling for baseline weight. However, active rTMS treatment did not improve the psychotic symptoms compared to sham stimulation. Conclusion: Our results suggest that add-on HF rTMS could be an effective therapeutic strategy for body weight control in patients with chronic SZ.
Keywords: Schizophrenia